2021
DOI: 10.3389/fpls.2021.698443
|View full text |Cite
|
Sign up to set email alerts
|

The THO/TREX Complex Component RAE2/TEX1 Is Involved in the Regulation of Aluminum Resistance and Low Phosphate Response in Arabidopsis

Abstract: The C2H2-type zinc finger transcription factor SENSITIVE TO PROTON RHIZOTOXICITY 1 (STOP1) plays a critical role in aluminum (Al) resistance and low phosphate (Pi) response mainly through promoting the expression of the malate transporter-encoding gene ARABIDOPSIS THALIANA ALUMINUM ACTIVATED MALATE TRANSPORTER 1 (AtALMT1). We previously showed that REGULATION OF ATALMT1 EXPRESSION 3 (RAE3/HPR1), a core component of the THO/TREX complex, is involved in the regulation of nucleocytoplasmic STOP1 mRNA export to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Recently, Guo et al (2020) found that HPR1 is involved in the regulation of Al resistance and low Pi response partly through the modulation of nucleocytoplasmic STOP1 mRNA export [101]. Another core component of the THO complex, RAE2/TEX1, has also been found to regulate Al resistance and low Pi response [102]. However, RAE2 did not affect STOP1 mRNA accumulation in the nucleus, although STOP1 protein level was reduced in rae2.…”
Section: Regulatory Factors Involved In Almt1 and Mate1 Expressionmentioning
confidence: 99%
“…Recently, Guo et al (2020) found that HPR1 is involved in the regulation of Al resistance and low Pi response partly through the modulation of nucleocytoplasmic STOP1 mRNA export [101]. Another core component of the THO complex, RAE2/TEX1, has also been found to regulate Al resistance and low Pi response [102]. However, RAE2 did not affect STOP1 mRNA accumulation in the nucleus, although STOP1 protein level was reduced in rae2.…”
Section: Regulatory Factors Involved In Almt1 and Mate1 Expressionmentioning
confidence: 99%
“…Thus, instead of full length EDS8 protein (also named THO1 and HPR1), a truncated version of it was produced in the eds8 mutant (Figure 3C). The At5g09860 encodes a component of the THO/TREX complex and has been identified in several studies to regulate plant responses to stresses including phosphate starvation, aluminum resistance, and plant basal defense [22,[29][30][31][32]. To further confirm that At5g09860 is the underlying gene for the SA and JA insensitive phenotypes of the eds8 mutant, we used another mutant allele of At5g09860, hpr1-5, which has the same mutation as eds8, to check if it showed similar responses to SA and JA [33].…”
Section: Identification Of Eds8 Gene Using Mapping-by-sequencingmentioning
confidence: 99%
“…The THO/TREX complex is conserved in yeast, plants, and animals [22]. In plants, it has been shown to regulate plant responses to stresses including phosphate starvation and aluminum toxin [22]. The involvement of THO/TREX complex in SA and JA signaling was further confirmed by checking the mutant phenotypes of another THO/TREX component, THO3.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, the ubiquitin ligase RAE1 (REGULATION OF ALMT1 EXPRESSION1) and RAH1 (RAE1 homolog1), the SUMO (small ubiquitin-related modifier) E3 ligase SIZ1 (SAP and MIZ1 domain-containing ligase1), and the SUMO protease ESD4 (EARLY IN SHORT DAYS4) are regulators of STOP1 abundance ( Godon et al, 2019 ; Zhang et al, 2019 ; Fang et al, 2021a , b ; Xu et al, 2021 ), and STOP1 is SUMOylated in planta ( Fang et al, 2020 ). Furthermore, hyperrecombination protein 1 (HPR1) and TEX1, two proteins of the conserved THO/TREX complex involved in transcription, messenger RNA (mRNA) processing, and nucleocytoplasmic export of transcripts also reduce STOP1 abundance ( Guo et al, 2020 ; Zhu et al, 2021 ). Apart from these proteins, which are not specific to STOP1 signaling, we do not know the steps upstream of STOP1 in this pathway, in particular, the Al-sensing mechanism.…”
Section: Introductionmentioning
confidence: 99%